The androecium of Adenium obesum (Apocynaceae): anther and pollen grains development - Campos, Deborah Cristina Dias; Possobom, Clivia Carolina Fiorilo; Almeida, Elka Fabiana Aparecida; Ramos, Sabrina Maihave Barbosa; Nietsche, Silvia (Ornamental Horticulture, 2025)
In this study, we describe anther development in Adenium obesum, providing information on microsporogenesis, microgametogenesis, and the structure of mature pollen grains. Buds and flowers at various developmental stages were collected from cultivated plants of an accession characterized by a simple, pink corolla. The samples were processed following standard protocols for light microcopy analysis, including histochemical tests, to identify starch and lipids. The androecium of A. obesum comprises five epipetalous stamens with anthers arranged in a conical structure that covers the apex of the style. The stamens are adnate to the petals through short filaments and are connected to the style head through unicellular trichomes, forming the gynostegium. The anthers are dithecous, tetrasporangiate, and longitudinally dehiscent. The development of parietal layers follows the dicotyledonous pattern, with the mature anther wall comprising an epidermis, endothecium, two to three middle layers, and secretory tapetum. The tetrads exhibit a tetrahedral arrangement, and cell division is of the simultaneous type. The pollen grains are bicellular, contain starch reserves, and are dispersed as monads, held together by a lipophilic substance. In the access studied here, no evidence of male sterility was observed. The main events during anther and pollen grain development in A. obesum were categorized as pre-meiotic, meiotic, and post-meiotic, and were correlated with the collection stages examined in this study. Our results provide morphological markers for these processes and can aid in implementing in vitro anther or microspore culture techniques, which are promising alternatives for the genetic improvement of the species.